The Role Of Community Mentoring In The Implementation Of Counseling For Child Clients Undergoing The Conditional Release Program In The Class I Community Center In Medan - Lindawati Br Surbakti; Yasmirah Mandasari Saragih; Sumarno Sumarno; Muhammad Mujahidin Za; Sukardi Sukardi (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
Children are part of the young generation who are the successors of the ideals of the nation's struggle and human resources for national development. Currently, violations of the law or criminal acts are not only committed by adults, but criminal acts committed by children are increasingly common. Every child who violates legal rules or commits a criminal act will be subject to sanctions in the form of criminal sanctions. Every child who is 14 (fourteen years old) but not yet 18 (eighteen years old) who is undergoing guidance at a Special Children's Development Institution is called a Foster Child. Every child who has undergone guidance in the LPKA has the right to obtain their rights, especially to obtain conditional release. According to Minister of Law and Human Rights Regulation Number 16 of 2023, conditional release can be granted to children who are serving a prison sentence at LPKA but who have met the requirements. The granting of Parole stages is carried out by the Correctional Center through Community Counselors. Community Counselors play an important role in implementing recommendations for the Parole program, including starting from the initial stages of proposing Parole, making Community Research (Litmas), carrying out guidance to ending guidance at the Correctional Center.